Ageing in Place: between Autonomy and Social Support. : Contributions of Cohousing and Coliving from a Comparative European Analysis ("Temas Sociais" Journal, 2025)
Population ageing poses increasing challenges to social policies, welfare systems and traditional housing models, requiring responses that promote autonomy, social integration and quality of life in later life. This article analyses the social, economic and housing conditions of older adults in Southern Europe and Scandinavia through a secondary analysis of data from the European Social Survey (2010), interpreted in light of the concepts of ageing in place, cohousing and coliving. A quantitative, exploratory and comparative methodology is adopted, focusing on variables such as economic conditions, household composition, co-residence and perceptions of loneliness.The findings reveal significant structural differences between the two regions, particularly regarding the role of family support, the strength of welfare systems and experiences of autonomy and social isolation. The analysis suggests that cohousing may represent a more structurally relevant response in contexts characterised by economic vulnerability and reliance on informal support, while coliving appears as a complementary solution, better suited to specific profiles of older adults with higher levels of autonomy. The article also highlights the central role of Social Work in mediating between individuals, communities and public policies, contributing to the development of housing responses tailored to the social inequalities of contemporary ageing.
Keywords: Ageing; Ageing in place; Cohousing; Coliving; Social inequalities; Social Work